Growth and yield of tomato plants (Lycopersicum esculentum Mill) grown in soil media containing several doses of inorganic fertilizers and sprayed with Lombok brown algae extracts. Issue 1 (January 2021) - Sunarpi, H; Nikmatullah, A; Sunarwidhi, A L; Ambana, Y; Ilhami, B T K; Widyastuti, S; Hernawan, A; Prasedya, E S
Abstract: Excessive use of inorganic fertilizers in the production of horticultural crops, increases production costs, decreases soil fertility and damages the environment. This article reports the growth and yield of tomato plants grown in soil media containing several doses of inorganic fertilizers and sprayed with Lombok brown algae extract. Tomato plants are grown in soil media containing inorganic fertilizers at a dose of 0, 50% or 100%. Then, each treatment plant was sprayed with 10% Lombok brown algae extract once a week during vegetative growth. The results showed that each Lombok brown algae extract had the same effect on NPK absorption, growth and yield of tomato plants. However, the effect of algae extracts on the absorption of essential elements, growth and yield of tomato plants is highly dependent on the dose of inorganic fertilizers supplied in the soil medium. The absorption of essential elements, growth and crop yields significantly increased in plants grown in soil medium containing 50% inorganic fertilizers and sprayed with 10% Lombok brown algae extract, compared to plants containing 0 inorganic fertilizers. This shows that the use of inorganic fertilizers can be reduced to 50% as long as the plants are sprayed with 10% Lombok brown algae extract.